Solid phase extraction using SiO2/Al2O3/TiO2 ternary oxide for Cu2+ preconcentration - Pinheiro, Evelyn F.; Rodrigues, José Guilherme A. [UNESP]; Honório, Gláucio G.; da Cunha, Jéssica N.; de Paula, Carlos Eduardo R.; de Andrade, Débora F.; Ribeiro, Emerson S. [UNESP]; D’Elia, Eliane (Sociedade Brasileira de Quimica (SBQ), 2019)
The present work aims at studying the preconcentration of Cu2+ ions by solid phase extraction using SiO2/Al2O3/TiO2 ternary oxide as adsorbent material. This methodology consists of the affinity of the analyte for the adsorbent material and its subsequent elution with the least amount of solvent. Subsequently, the aqueous phase containing the extracted analyte was collected and analyzed by square wave anodic stripping voltammetry (SW-ASV). For the applied solid phase extraction (SPE) methodology, a complete factorial design was carried out with 3 variables at 2 levels (pH, elution flow rate and analyte concentration) to optimize the extraction conditions. The results showed that at pH 9, the SiO2/Al2O3/TiO2 oxide presents excellent Cu2+ adsorption capacity with recovery values between 81.0 and 104% for this pH range. The limit of detection (LOD) and limit of quantification (LOQ) values were determined to be 1.71 and 5.64 μg L-1, respectively. The study of recovery for SPE method revealed results of 102 and 103%.
Keywords: Cachaça; Copper ions; Preconcentration; Solid phase extraction; Square wave anodic stripping voltammetry; Ternary oxide